Indonesia's Defense Policy In Addressing Space Threats In Perspective Of Defense Management - Brahmana, Dedy Putra; Anak Agung Banyu Perwita; Agus Sudarya; Hikmat Zakky Almubaroq (CV. AFDIFAL MAJU BERKAH, 2024)
This article investigates Indonesia's defense policy in addressing space threats, driven by the research objectives of analyzing the policy, assessing its effectiveness, and providing recommendations for improvement. Employing a qualitative research method with an analytical descriptive design, the study explores Indonesia's approach to space security through an extensive review of legal and strategic documents. The research highlights key components, including foundational laws emphasizing the protection of sovereignty and the recognition of the Fourth Industrial Revolution's impact on defense, leading to the expansion of the defense domain into cyberspace and space. Strategies involve modernization, resilience, and the nurturing of domestic space capabilities. The analysis reveals challenges, such as the rapid evolution of space technology, resource allocation, coordination, international partnerships, human capital development, and managing the dual-use nature of space technology. Indonesia's defense policy aligns with broader defense and security objectives, emphasizing the importance of space in safeguarding national sovereignty and promoting economic growth. The study concludes that continuous adaptation, coordination, and international collaboration are vital to effectively mitigate space threats and secure the nation's interests in the 21st century. The utilization of space has expanded in the modern age. Indonesia is looking to space to overcome its geographical challenges. However, Indonesia must formulate defense policy to address emerging threats. This research problems are comprehending Indonesia's defense policy in addressing space threats and evaluating the effectiveness of the existing policy. The objectives are to analyze the policy and assess its effectiveness. Employing a qualitative literature research method with analytical descriptive design, the research subject is Indonesian Defense Ministry. The object is Indonesia's defense policy in addressing space threats. The research result highlights laws emphasizing the protection of sovereignty and the recognition of the Fourth Industrial Revolution's impact on defense, leading to the expansion of the domain into cyberspace and space. Strategies involve modernization, resilience, and the nurturing of space capabilities. The analysis reveals challenges, such as rapid evolution of space technology, resource allocation, coordination, international partnerships, human capital development, and dual-use nature of space technology management. Indonesia's defense policy aligns with broader defense and security objectives, emphasizing the importance of space in safeguarding national sovereignty and promoting economic growth. The study concludes that continuous adaptation and international collaboration are vital to effectively mitigate space threats and secure the nation's interests.